Kebutuhan Desain Awal Pada Pilot Plant Pengolahan Monasit Menjadi Thorium Oksida (ThO2) - Nuri, Hafni Lissa; Prayitno, Prayitno; Jami, Abdul; Pancoko, Marliyadi (BRIN Publishing, 2014)
Data and information collection aimed in order to meetthe needs ofthe initial designfor pilot plantof monazite processing into thorium oxide (ThO2). The content ofthorium inmonaziteis high in Indonesia between 2.9 to 4.1% andrelatively abundantin Bangka Belitung Islands. Thorium can be used as fuel because of its potential is more abundant instead of uranium. Plant of thorium oxide commercially from monazite established starting from pilot plant in order to test laboratory data. Pilot plant design started from initial design, basic design, detailed design, procurement and construction. Preliminary design needs includes data feed and products, a block diagram of the process, a description of the process, the determination of process condition sand type of major appliance has been conducted.